The construction of an urban-regional university system in bogotá (2010)
This paper explores the possibilities for a regionalurban university system for Bogotá city, starting from actual conditions of higher education campuses and those projected, searching the way to harmonize them with the regional- urban model proposed by the Territory Ordering Plan actualized on 2004. The aim of this article is to establish conceptual and territorial basis of a system of university equipments to match the big territorial issues defined for 10 year ahead in the city related to social equity, competitiveness, academic and technique qualification of population, as well as the improvement of scientific and technologic development of the city at the prospect of the Master Plan for Higher Education defined by the Territory Ordering Plan.